A Single‐Droplet Electricity Generator Achieves an Ultrahigh Output Over 100 V Without Pre‐Charging. Issue 51 (15th October 2021) - Zhang, Qi; Li, Yahui; Cai, Han; Yao, Mingfang; Zhang, Haodong; Guo, Linqi; Lv, Zhenjie; Li, Mengqiu; Lu, Xichi; Ren, Chao; Zhang, Penglei; Zhang, Yanxin; et al.
Abstract: The working principle of the triboelectric nanogenerator (TENG), contact electrification and electrostatic induction, has been used to harvest raindrop energy in recent years. However, the existing research is mainly concentrated on solid–liquid electrification, and adopts traditional electrostatic induction (TEI) for output. As a result, the efficiency of droplet electricity generators (DEGs) is severely constrained. Therefore, previous studies deem that the DEG output is limited by interfacial effects. This study reveals that this view is inappropriate and, in reality, the output strategy is the key bottleneck restricting the DEG performance. Here, a switch effect based on an electric‐double‐layer capacitor (EDLC) is introduced, and an equivalent circuit model is established to understand its working mechanism. Without pre‐charging, a single droplet can generate high voltage over 100 V and the output is directly improved by two‐orders of magnitude compared with TEI, which is precisely utilizing the interfacial effect. This work provides insightful perspective and lays solid foundation for DEG applications in large scale. Abstract : A droplet electricity generator (DEG) combining interfacial effect and switch effect is proposed to achieve an ultrahigh output without pre‐charging, and the working mechanism is explained based on an equivalent circuit model. Compared with traditional electrostatic induction (TEI) electricity generation, the output is directly improved by two orders of magnitude, which provides insightful perspective and lays a solid foundation for large‐scale DEG applications.